2019
DOI: 10.1080/02656736.2019.1690169
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasound- and laparoscopy-guided percutaneous microwave ablation for adenomyosis: preliminary results

Abstract: Purpose: Adenomyosis is a relatively common disease among women of childbearing age. A minimally invasive alternative technique with low risks, faster recovery and decreased side effects is desired. We hypothesized that percutaneous microwave ablation (PMWA) under laparoscopic guidance would substantially reduce the risk of collateral thermal damage to the intestinal tract and relieve the pelvic adhesions. This study aimed to evaluate the feasibility, safety and efficacy of transvaginal ultrasoundand laparosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The uterine volume and nidus reduction rates are also important evaluation indexes for the effect of microwave ablation of adenomyosis. Liu et al (15) observed the uterine volume reduction rate after microwave ablation in 70 patients with adenomyosis; after 1, 6, and 12 months, the reduction rate was 28.2%, 50.6%, and 55.2%, respectively. In patients with adenomyosis, Lin et al (16) reported uterine volume reduction rates of 44.8% and 64.9% at 3 and 12 months after microwave therapy, respectively, which were better than those after radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uterine volume and nidus reduction rates are also important evaluation indexes for the effect of microwave ablation of adenomyosis. Liu et al (15) observed the uterine volume reduction rate after microwave ablation in 70 patients with adenomyosis; after 1, 6, and 12 months, the reduction rate was 28.2%, 50.6%, and 55.2%, respectively. In patients with adenomyosis, Lin et al (16) reported uterine volume reduction rates of 44.8% and 64.9% at 3 and 12 months after microwave therapy, respectively, which were better than those after radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, according to accurately positioned contrast-enhanced ultrasound, the ablation was supplemented immediately, and contrastenhanced ultrasound was performed again 1 to 2 days after the procedure; the ablation rates rose to 92%, 93%, and 95%, respectively. In their study, Xu et al (19)(20)(21)(22)(23) compared the difference in the microwave ablation effect between contrast-enhanced ultrasound and enhanced MRI, and found that contrast-enhanced ultrasound could be used to accurately evaluate the ablation rate of local adenomyosis following microwave ablation, with the consequence being consistent with that of enhanced MRI. Contrast-enhanced ultrasound is a simple, real-time, dynamic, and cost-effective method, which is more suitable for timely evaluation after microwave ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 38 articles , met all inclusion criteria and were included in this meta-analysis. The types of ablation were HIFU in 28 studies , PMWA in five studies [46][47][48][49][50] and RFA in four studies [51][52][53][54]. Besides, one study [45] compared PMWA with RFA in the management of AD.…”
Section: Literature Searchmentioning
confidence: 99%
“…The incidence of minor adverse events was 39.0%, 51.3% and 3.6% after HIFU, PMWA and RFA, respectively. The main minor adverse events were transient sciatic nerve pain, transient unilateral leg weakness, transient hematuria, skin burn, vaginal bleeding and lower abdominal pain in the HIFU group [19][20][21]24,26,28,[35][36][37], and transient macroscopic hematuria, vaginal discharge and lower abdominal pain in the PMWA and RFA groups [46][47][48]51,52,54]. Although all cases were minor and recovered without any permanent adverse effects, these events revealed thermal injury to the surrounding tissues, such as the sciatic nerve, bladder, endometrium, bowel and abdominal skin.…”
Section: Main Findings and Comparison With Existing Literaturementioning
confidence: 99%